Os efeitos danosos do crime organizado e da corrupção dos agentes públicos e privados no desenvolvimento econômico do país - Abelha, Carlos Fernando Lopes (2011)
This essay addresses issues such as socio-economic system adopted by the Republican Constitution of 1988; free enterprise as a fundamental right, seen by the matrix of the economic order, and the privatization process of the Federal Government as a strategy to reform the state, to serve as a basis to elucidate, within a factual context, the negative consequences to public rail transport, transferred to private enterprise in 1998, according to the National Privatization Program of the Federal Government, caused by abuse of the exercise of free enterprise and the inefficient management of public and private agents. It was found that the process of privatization of this service, previously performed by the Federal Railway - RFFSA occurred in studies of the National Bank of Economic and Social Development, which showed high public deficit and other causes that justified its transfer to the private enterprise. Through bibliographies literature researches, and extensive official documentation produced by public servants of the Federal Railway Police, the National Department of Transport Infrastructure in the National Agency for Land Transport, and other federal agencies, numerous surveys on spots made along the Paulista Railway Network in the years 2008/2009, demonstrating the damage caused to all rail transport system and public coffers, pointing out its causes and actions to solve them. The survey s results conducted on locations that have left traces (patios, garages, railway stations and substations) have been duly listed, following the investigation project and, submitted to engineering experts, computing and accounting examination, the results were analyzed and compared with the legal system and with the goals proposed by the privatization and concession of public service in question. It demonstrates the practice of illegal conduct by public and private agents involved in the supervision and implementation of this public service, intentional noncompliance of the terms of that contract, breach of criminal law and the Law of Concessions and Permits, whose consequences are highly detrimental to Public Service and National Treasury. At the conclusion of this paper it presents the main actions to be taken to solve the problems and to blame the culprit in order to improve the public service